Self-Assembled Cationic-Covered Nanoemulsion as A Novel Biocompatible Immunoadjuvant for Antiserum Production Against Tityus serrulatus Scorpion Venom - Arthur Sérgio Avelino de Medeiros; Manoela Torres-Rêgo; Ariane Ferreira Lacerda; Hugo Alexandre Oliveira Rocha; Eryvaldo Sócrates Tabosa do Egito; Alianda Maira Cornélio; Denise V. Tambourgi; Matheus de Freitas Fernandes-Pedrosa; Arnóbio Antônio da Silva-Júnior (MDPI AG, 2020)
This study assesses the efficacy of different nanoemulsion formulations as new and innovative adjuvants for improving the in vivo immunization against the Tityus serrulatus scorpion venom. Nanoemulsions were designed testing key-variables such as surfactants, co-solvents, and the influence of the temperature, which would be able to induce the phase transition from a liquid crystal to a stable nanoemulsion, assessed for four months. Additionally, cationic-covered nanoemulsion with hyper-branched poly(ethyleneimine) was prepared and its performance was compared to the non-cationic ones. The physicochemical properties of the selected nanoemulsions and the interactions among their involved formulation compounds were carefully monitored. The cytotoxicity studies in murine macrophages (RAW 264.7) and red blood cells were used to compare different formulations. Moreover, the performance of the nanoemulsion systems as biocompatible adjuvants was evaluated using mice immunization protocol. The FTIR shifts and the zeta potential changes (from −18.3 ± 1.0 to + 8.4 ± 1.4) corroborated with the expected supramolecular anchoring of venom proteins on the surface of the nanoemulsion droplets. Cell culture assays demonstrated the non-toxicity of the formulations at concentrations less than 1.0 mg/mL, which were able to inhibit the hemolytic effect of the scorpion venom. The cationic-covered nanoemulsion has shown superior adjuvant activity, revealing the highest IgG titer in the immunized animals compared to both the non-cationic counterpart and the traditional aluminum adjuvant. In this approach, we demonstrate the incredible potential application of nanoemulsions as adjuvants, using a nanotechnology platform for antigen delivery system on immune cells. Additionally, the functionalization with hyper-branched poly(ethyleneimine) enhances this recognition and improves its action in immunization.